Beyond residential mobility: A broader conceptualization of instability and its impact on victimization risk among children. (May 2018) - Merrick, Melissa T.; Henly, Megan; Turner, Heather A.; David-Ferdon, Corinne; Hamby, Sherry; Kacha-Ochana, Akadia; Simon, Thomas R.; Finkelhor, David
Abstract: Predictability in a child's environment is a critical quality of safe, stable, nurturing relationships and environments, which promote wellbeing and protect against maltreatment. Research has focused on residential mobility's effect on this predictability. This study augments such research by analyzing the impact of an instability index—including the lifetime destabilization factors (LDFs) of natural disasters, homelessness, child home removal, multiple moves, parental incarceration, unemployment, deployment, and multiple marriages--on childhood victimizations. The cross-sectional, nationally representative sample of 12, 935 cases (mean age = 8.6 years) was pooled from 2008, 2011, and 2014 National Surveys of Children's Exposure to Violence (NatSCEV). Logistic regression models controlling for demographics, socio-economic status, and family structure tested the association between excessive residential mobility, alone, and with LDFs, and past year childhood victimizations (sexual victimization, witnessing community or family violence, maltreatment, physical assault, property crime, and polyvictimization). Nearly 40% of the sample reported at least one LDF. Excessive residential mobility was significantly predictive of increased odds of all but two victimizations; almost all associations were no longer significant after other destabilizing factors were included. The LDF index without residential mobility was significantly predictive of increased odds of all victimizations (AOR's ranged from 1.36 to 1.69), and the adjusted odds ratio indicated a 69% increased odds of polyvictimization for each additional LDF a child experienced. The LDF index thus provides a useful alternative to using residential moves as the sole indicator of instability. These findings underscore the need for comprehensive supports and services to support stability for children and families.